Loss assessment of fruit and vegetables in selected public markets in Davao del Sur, Bukidnon, and Cagayan de Oro - Bayogan E.V; Urquiola M.A.J; Secretaria L.B; Bello D.D.; Sampiano K.F.S (CGIAR, 2023)
Horticultural crops, particularly fruits and vegetables, have played a significant role in ensuring food security (Weinberger and Lumpkin, 2007). They offer abundant and cost effective sources of essential nutrients like fiber, vitamins, minerals, and antioxidants (Rajani and Joshi, 2017). Vegetable crops are crucial for developing countries, contributing to income and nutrition. (Tadese, 2023). However, horticultural produce is highly perishable and prone to postharvest losses, leading to an estimated 1.3 billion tons of agricultural waste during distribution activities worldwide (Augustin et al., 2020). These losses not only affect market availability but also increase prices and environmental footprints. Losses and waste of fruits and vegetables pose a challenge to the food supply chain, impacting food security and causing negative social, economic, and environmental consequences (Anand and Barua, 2022). Fruits and vegetables experienced the most substantial loss and waste, accounting 25-50% of the total production (Bancal and Roy, 2022).